2013
DOI: 10.1111/jgh.12319
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant cytokeratin expression as a possible prognostic predictor in poorly differentiated colorectal carcinoma

Abstract: CK20 status may be used as a prognostic predictor of PDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
(59 reference statements)
0
18
1
Order By: Relevance
“…Yamagishi et al paid specific attention to CRCs with variant histology (i.e., poorly differentiated, mucinous, signet ring, etc.). The authors found a negative prognostic significance for CK20 expression in poorly differentiated carcinomas, while this association was not found in well/moderately differentiated CRCs or in CK7 18 . In concordance with our results, the authors showed increased CK20 expression in MMR proficient tumors, which is in line with previously published studies 8 , 14 , 15 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Yamagishi et al paid specific attention to CRCs with variant histology (i.e., poorly differentiated, mucinous, signet ring, etc.). The authors found a negative prognostic significance for CK20 expression in poorly differentiated carcinomas, while this association was not found in well/moderately differentiated CRCs or in CK7 18 . In concordance with our results, the authors showed increased CK20 expression in MMR proficient tumors, which is in line with previously published studies 8 , 14 , 15 .…”
Section: Discussionmentioning
confidence: 88%
“…Yamagishi et al used a cut-off value of 1% for CK7 and 25% for CK20. The authors argue that since normal colonic mucosa does not express CK7 and only show diffuse expression of CK 20, any CK7 expression should be considered abnormal even at 1%, and CK20 < 25% should be evaluated as abnormally downregulated 18 . The point concerning CK20 is reasonable from our point of view, but for CK7, we think that expression in < 10% of tumor cells barely represents a significant expression since we had some cases in which CK7 + staining was only present in single cells, which in the words of Harbaum et al could be a “freak of nature” 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary Metastasectomy for mCRC in Brazil [34,35]. A possible explanation is that these observations were performed in localized instead of metastatic colorectal cancer, thus limiting generalizability of this finding to our sample.…”
Section: Discussionmentioning
confidence: 99%
“…CK7 is expressed in several simple ductal and glandular epithelia, including the lung, breast, bile and pancreatic ducts, urinary tracts, ovary and endometrium (27). In contrast, CK7 expression is generally lacking in normal mucosa of the colon, rectum and, correspondingly, in colorectal adenoma and adenocarcinoma (11,28).…”
Section: Discussionmentioning
confidence: 99%